Assessing Integrated Public Service Innovation Through Comparative Public Service Mall Governance in Indonesia - Adelia Ramadani; Herman H (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This research assesses integrated public service innovation by comparing the governance of Public Service Malls (MPPs) in Pati Regency, Jayapura City, and Singkawang City.Utilizing a qualitative approach based on literature analysis, the study employs the Public Service Innovation Theory to assess innovation's contribution across process, organizational, technology, and policy dimensions in enhancing public value and service quality. The findings reveal varied innovation patterns, dependent on the institutional capacity and digital readiness of the respective regions. The Pati Regency MPP faces hurdles like limited digital infrastructure, reliance on unstable central government websites, and a location that hinders inter-agency collaboration. The Jayapura City MPP shows better effectiveness but requires strengthening in human resources, supporting infrastructure, and cross-agency coordination. Conversely, the Singkawang City MPP's main challenge is low service socialization via digital media and minimal public participation, with citizens opting for direct office access. The study concludes that optimal public service innovation requires robust organizational capacity, adequate integration of information technology, and adaptive regulation. This research affirms the relevance of the Public Service Innovation Theory in understanding public sector innovation dynamics, offering a conceptual contribution to developing a more holistic, responsive, and public-value-oriented MPP governance model.